Odpowiedzialność karna parlamentarzysty za zachowania się prowadzące de facto do nielegalnej zmiany konstytucyjnego ustroju Rzeczypospolitej Polskiej - Zacharski, Michał (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The article concerns the problem of criminal responsibility for parliamentarian’s conventional acts in the legislative process, primarily voting, which result in the adoption of a normative act whose content remains in conflict with constitutional norms to such an extent that it means the factual illegal change of the constitutional system of the state with the circumvention of the procedure provided for in the constitution. The author analyses the issue from the perspective of the concepts of excess of authority and neglect of duty. The study includes considerations concerning the contents and scope of application of parliamentary immunity.